Vocational interests of computer programmers. - Perry, Dallis K.; Cannon, William M.; Perry, D K; Cannon, W M (Journal of Applied Psychology)
The revised SVJB was administered to 1,378 computer programmers. Primary analyses were limited to 1,003 males with at least 2 yr. of programming experience, whose jobs were primarily non-supervisory, and who indicated satisfaction with programming. Programmers differ from other professional men primarily in their greater interest in problem solving, mathematics, and mechanical pursuits, and their lesser interest in people. Their interests are most similar to optometrists, chemists, engineers, production managers, mathematics- science teachers, and senior CPAs; but none of these existing keys adequately represents the interests of programmers. A Programmer key developed on half the sample and evaluated on the remaining half discriminates well between programmers and men in general. Satisfied programmers score significantly higher on the key than dissatisfied programmers.